Community Empowerment for the Society at Bringsang Village, Gili Genting in Utilizing Mangrove Coffee (Rhizophore Stylosa) Commodities - Chandra, Adyos Bobby; Yogi N, Duwi Karisma; Abida, Indah Wahyuni; Alfisuma, Meria Zakiyah; Zakiyah, Fitriyatuz (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
The potential of the mangrove forest ecosystem along Bringsang Village, Gili Genting District, Sumenep Regency's coast has not been optimally utilized. Therefore, this community engagement has a purpose to give training how to make mangrove coffee. This engagement was conducted at the Bringsang Village Hall on October 21, 2023, with 15 participants, including local residents and village officials. The Rhizophora stylosa mangrove species is one of the important commodities that can be presented as mangrove coffee. This community engagement activity aims to increase knowledge and train the community in making mangrove coffee. The method used is the practice of making mangrove coffee and interviewing the residents of Bringsang Village, Gili Genting. The result of the activity is a procedure for processing Rhizophora stylosa mangrove fruit into coffee powder. Mangrove coffee is priced at IDR 5,000 per pack. The community and village officials were very enthusiastic about the training in making Bringsang Village's signature mangrove coffee.